Fabrication of Different Types of Photodetectors Based on Carbon Quantum Dots/Alq3 Organic Material - Mina Mohammed Jawad; Lamees A. Abdullah (Iraqi Journal of Physics)
In this work, the properties of the photodetector were improved by using carbon quantum dots (CQDs) and tris (8-hydroxyquinoline) aluminium (III) (Alq3) polymer when deposited on glass and silicon substrates. CQDs were prepared using an electrochemical method. Two methods of deposition were used; the first was drop casting, and the other was spin coating. The structural, electrical, and optical properties were studied. Measurements were made of the manufactured photoconductive detector's current-voltage (I–V) properties, photocurrent gain, response time, and quantum efficiency, responsivity. The constructed detector's performance was measured without light and using a 250-watt tungsten lamp, whose wavelength range was between 500 and 800 nm. The results showed that the best photodetector was when carbon quantum dots were used with Alq3 deposited on a silicon substrate using the drop-casting method (CQD:Alq3/Si). It was observed that the best gain, fastest rise, fall, and response times were 7.97, 0.98, 1.1, and 0.34 s, respectively.